Observation of the Orientation of Snow Hydrometeors at Sheltered and Unsheltered Sites - J. Grazioli; M. Condolf; Y.‐A. Roulet; F. Coletti; A. Berne (Geophysical Research Letters)
Abstract Knowledge about orientation of falling snow is still poorly documented with field measurements despite its importance, for example, in the interpretation of remote sensing data. This study investigates the orientation of snow hydrometeors using data from a Multi‐Angle Snowflake Camera. We explore the impact of different observational setups (sheltered vs. unsheltered), wind speed, hydrometeor type, and axis ratio on the orientation distributions. Numerical simulations are used to select the best orientation estimator and to understand the reason behind contrasting results reported in past literature. We find that previously reported non‐zero median orientations are likely artifacts due to averaging absolute values of orientations from the three individual cameras. Observed orientations generally follow a symmetrical distribution around 0°, with broader distributions observed at unsheltered sites and/or high wind conditions. Observed distributions may vary significantly from those assumed in previous studies, highlighting the need for further research on hydrometeor orientations under varying environmental conditions.